Human leukocyte antigen (HLA)-F and -G gene polymorphisms and haplotypes are associated with malaria susceptibility in the Beninese Toffin children - Sonon, Paulin; Tokplonou, Léonidas; Sadissou, Ibrahim; M'po, Kuumaaté K.G.; Glitho, Sonya S.C.; Agniwo, Privat; Ibikounlé, Moudachirou; Souza, Andréia S. [UNESP]; Massaro, Juliana Doblas; Gonzalez, Daniel; Tchégninougbo, Théophile; Ayitchédji, Aurèle; et al. (Elsevier, 2021)
Background: Little attention has been devoted to the role of the immunoregulatory HLA-E/-F/−G genes in malaria. We evaluated the entire HLA-E/-F/−G variability in Beninese children highly exposed to Plasmodium falciparum (P.f.) malaria. Methods: 154 unrelated children were followed-up for six months and evaluated for the presence and number of malaria episodes. HLA-E/-F/−G genes were genotyped using massively parallel sequencing. Anti P.f. antibodies were evaluated using ELISA. Results: Children carrying the G allele at HLA-F (−1499,rs183540921) showed increased P.f. asymptomatic/symptomatic ratio, suggesting that these children experienced more asymptomatic P.f. episodes than symptomatic one. Children carrying HLA-G-UTR-03 haplotype exhibited increased risk for symptomatic P.f. episodes and showed lower IgG2 response against P.f. GLURP-R2 when compared to the non-carriers. No associations were observed for the HLA-E gene. Conclusion: HLA-F associations may be related to the differential expression profiles of the encoded immunomodulatory molecules, and the regulatory sites at the HLA-G 3'UTR may be associated to posttranscriptional regulation of HLA-G and to host humoral response against P.f.
Keywords: Antibody; Haplotype; HLA-Ib; Plasmodium falciparum; SNV